"Get that Camera out of my Face!" A Look at Children, Privacy and the Broadcasting Standards - des Tombe, Micheal (Victoria University of Wellington Law Review, 2000)
This article looks at the current national and international law surrounding children’s rights to privacy in broadcasting. It examines issues of consent, both of the parent and the child, as well as public interest defences where consent is absent. The article concludes that the Broadcasting Standards Authority should develop a new and separate broadcasting code for children’s privacy rights based partly on overseas precedents.